Induksi Protocorm pada Eksplan Bawang Putih pada Media MS Minim Hara Makro dan Mikro yang Ditambahkan Air Kelapa - Husain, Indriati (Jurnal Agroteknotropika, 2012)
This research aims to determine the occurrence on induction of protocorm in garlic on the media MS minimal macro and micro nutrient added coconut water. The materials used are garlic, coconut water and nutrient minimal macro and micro. The result was the establishment of direct induction of green protocorm from garlic explants. Conclusion of this research is the addition of 15% coconut water in medium MS minimal macro and micro nutrient can induce formation of protocorm directly from garlic explants.